PENGARUH TERAPI PERILAKU (TEKNIK MODELLING DAN TOKEN EKONOMI) TERHADAP FREKUENSI ENURESIS PADA ANAK USIA PRASEKOLAH (4-6 TAHUN) - Abd Wahid; Sri Yunita Suraida Salat (Wiraraja Medika : Jurnal Kesehatan, 2017)
Enuresisis urinary problem sare often found in childhood and cause concern for patients and their families. The results of preliminary studies that have been carried outin Apri l2014, of 10 children aged 4-6 years who were in the village of Sejati Slabayan District of Camplong Sampang found that 60% of children aged4-6 years experience denuresis and 40% did not experience enuresis. This study is an experimental pre-one group pretest-posttest design. Collecting data using pre and post observations. Data was taken on the majority of children who have enuresis of purposive sampling technique. The results were analyzed using descriptive and correlation parametric test paired t-test. The frequency of enuresis in children before and after behavior therapy there are significant differences. Analysis of parametric tes twith a variable scale paired t-test shows that there is influence between behavior therapy (modeling techniques and token economy) to decrease the frequency of enuresis(p=0.000). To further research the authors suggest that continued follow-up study with some preparation sinclude a clearand practical education to the respondent, the procurement of more stringent environmental controls, manufacture of detector surinate more flexible, so that it can be better.